2014
DOI: 10.1165/rcmb.2012-0465oc
|View full text |Cite
|
Sign up to set email alerts
|

Urban Particulate Matter Suppresses Priming of T Helper Type 1 Cells by Granulocyte/Macrophage Colony–Stimulating Factor–Activated Human Dendritic Cells

Abstract: Urban particulate matter (UPM) exacerbates asthmatic lung inflammation and depresses lung immunity. Lung dendritic cells (DCs) react to airway particulates, and have a critical role in linking innate and adaptive immunity, but the direct effects of UPM on DCs, that have been activated by granulocyte/macrophage colony-stimulating factor (GM-CSF), a product of stimulated normal human bronchial epithelial cells, has not been investigated. Human blood CD1c(+) DCs were purified and activated with UPM in the presenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
33
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 49 publications
2
33
0
1
Order By: Relevance
“…That such an effect is enhanced with GM‐CSF is in agreement with our current understanding for a pro‐inflammatory role for GM‐CSF in pollution‐induced lung disease 16, 18, 19. Although not the focus of this research, our finding of suppression of MHC class I expression by GM‐CSF is intriguing and deserves more detailed investigation in dedicated studies.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…That such an effect is enhanced with GM‐CSF is in agreement with our current understanding for a pro‐inflammatory role for GM‐CSF in pollution‐induced lung disease 16, 18, 19. Although not the focus of this research, our finding of suppression of MHC class I expression by GM‐CSF is intriguing and deserves more detailed investigation in dedicated studies.…”
Section: Discussionsupporting
confidence: 89%
“…Possible mechanisms by which air pollution might impair anti‐microbial immune responses have been identified to explain this association 36, 37. Indeed our previous work with DC‐stimulated naïve CD4 T lymphocytes showed decreased priming of IFN γ ‐producing CD4 T lymphocytes in similar experiments examining the effect of adding UPM to GM‐CSF‐treated mDCs 16. However, the present research with naive CD8 T lymphocytes, using a comparable experimental system, does not show UPM to impair priming of an IFN‐ γ ‐producing CD8 response, but in contrast demonstrates enhancement of this response.…”
Section: Discussionmentioning
confidence: 89%
“…To test the hypothesis that UPM stimulation of DCs (UPM-DCs) enhances T cell recall responses to allergen, Tms from patients with asthma with allergy to HDM were cocultured with autologous DCs pretreated overnight in the presence or absence of a fixed dose of UPM (previously optimized at 5 mg/ml [23]) with or without HDM (dose range 0-500 standardizedquality [SQ] units/ml). Cells were cultured for 5 days and IL-13 secretion in supernatants was measured by CBA.…”
Section: Upm-activated Dcs Activate Autologous Memory Cd4 T Cellsmentioning
confidence: 99%
“…We previously established that UPM directly matures human CD1c 1 myeloid DCs, which are the precursors of DCs that populate the lung mucosa and submucosa, and enhance the maturation induced by granulocyte/ macrophage colony-stimulating factor (GM-CSF), a product of UPM-stimulated AECs, that is essential for lung myeloid DC survival and differentiation (21,22). We found that UPM-activated DCs are capable of priming alloantigen-specific human naive CD4 T cell proliferation, but suppress the capacity of newly primed cells to produce Th1 and Th2 cytokines (23).…”
mentioning
confidence: 97%
“…Подтверждением этого служат литературные данные, свидетельствующие об авид-ности CTLA-4 к молекулам класса В7, в сотни раз превышающей авидность CD28 к тем же молеку-лам, поэтому при снижении экспрессии молекулы CD28 тормозное взаимодействие CTLA-4/B7 в ко-нечном итоге преобладает, что ведет к прекраще-нию иммунного ответа [12][13][14][15]. Еще в трех работах, опубликованных в 2015 году, авторы резюмируют свои исследования схожими выводами о том, что взаимодействие CD28, CTLA-4 с их лигандами CD80 и CD86 в процессе костимуляции является основополагающим фактором в индукции и супрес-сии иммунных ответов [16][17][18].…”
Section: Discussionunclassified